Pengaruh Ekstrak Mentimun, Formulasi Tepung Tapioka dan Ikan Kakap Putih terhadap Kecerahan Pempek Lenjer - Mukhtarudin Muchsiri; Alhanannasir Alhanannasir; Sri Agustini; Rika Puspita Sari MZ; Windi Windi (Jurnal Dinamika Penelitian Industri, 2022)
Pempek is a typical food from Palembang, South Sumatra, made from tapioca flour and ground fish meat, one of which is white snapper. One alternative effort to improve the color quality (brightness) of white snapper pempek is the addition of cucumber extract as well as water substitution in the manufacturing process. This study aims to determine the effect of cucumber extract, the ratio of tapioca flour and white snapper on the chemical quality (protein content) and physical quality (color L*, a*, b*) of pempek lenjer. The method used is factorial d2 factorial RAK, namely; (1) the addition factor of cucumber extract (K) and (2) the ratio of tapioca flour to white snapper (C), which formed six treatment combinations with 3 replications. Included were chemical tests in the form of protein content and physical tests in the form of color quality, lightness (L*), redness (a*) and yellowness (b*). The K1C1 treatment (addition of cucumber extract, 45% tapioca, and 55% white snapper) had the highest average protein content of 10.54%. The K2C3 treatment (water, 55% tapioca, and 45% white snapper) had the lowest average protein content of 6.89%. The addition of cucumber extract and the ratio of tapioca to white snapper meat had a significant effect on the lightness of pempek lenjer. The K1C3 treatment had the highest lightness value (63.17%), the lowest yellowness value (4.59%), and the lowest edness value (-5.41). The K2C2 treatment had the lowest lightness value (57.74%) and the highest yellowness value (7.38%). The highest redness value was found in the K1C2 treatment, which was -4.49. The addition of cucumber extract and the ratio of tapioca flour to white snapper had a significant effect on the lightness value of pempek lenjer.